Biphasic Plating – In vivo study of a novel fixation concept to enhance mechanobiological fracture healing. Issue 8 (August 2020) - Hofmann-Fliri, Ladina; Epari, Devakara R; Schwyn, Ronald; Zeiter, Stephan; Windolf, Markus
Highlights: A new biphasic plating concept has been developed to create reliable mechanical healing conditions and simultaneously improve implant strength Bones stabilized with a biphasic plate showed robust callus formation for transverse, oblique and offset fractures. All 18 sheep operated with a biphasic plate tolerated it well and no plate deformation or failures were observed under full weight bearing The results of this large animal study support in vivo feasibility of the biphasic plating concept Abstract: Background: Fracture fixation has advanced significantly with the introduction of locked plating and minimally invasive surgical techniques. However, healing complications occur in up to 10% of cases, of which a significant portion may be attributed to unfavorable mechanical conditions at the fracture. Moreover, state-of-the-art plates are prone to failure from excessive loading or fatigue. A novel biphasic plating concept has been developed to create reliable mechanical conditions for timely bone healing and simultaneously improve implant strength. This paper introduces the novel fixation concept and presents preclinical results from a large animal study. Methods: Twenty-four sheep underwent a mid-diaphyseal osteotomy stabilized with either the novel biphasic plate fixator or a control locking plate. Different fracture patterns regarding orientation and localization were investigated. Animals were free to fully bear weight during the post-operative period. After 12 weeks, the healing fractures were evaluated for bone formation using micro-computer tomography and strength and stiffness using biomechanical testing. Additionally, histological evaluation of soft tissue samples with respect to metal wear debris was performed. Results: No plate deformation or failures were observed under full weight bearing with the biphasic plate. Defects stabilized with the biphasic plate demonstrated robust callus formation compared to control group. Torsion tests after plate removal revealed no statistical difference in peak torsion to failure and stiffness for the different fracture patterns stabilized with the biphasic plate. However, the biphasic plate group specimens were 45% stronger (p=0.002) and 48% stiffer (p=0.007) than the controls. No histological signs of metal wear due to the biphasic feature could be found. Conclusions: The biphasic plate concept is aimed at improving the biomechanics of locked plating. The results of this large animal study demonstrate the feasibility and clinical potential of this novel stabilization concept.